A Best Practice Modular Design of a Hybrid Course Delivery Structure for an Executive Education Program. (January 2017) - Klotz, Dorothy E.; Wright, Thomas A.
ABSTRACT: This article highlights a best practice approach that showcases the highly successful deployment of a hybrid course delivery structure for an Operations core course in an Executive MBA Program. A key design element of the approach was the modular design of both the course itself and the learning materials. While other hybrid deployments may stress the importance of modular design, our deployment demonstrates how content can be easily mixed and matched into shorter courses on select topics. In particular, through the migration of select content online and the use of face‐to‐face class time for discussion and active‐learning experiences, we were able to dramatically reduce face‐to‐face student seat time, positively increase the student experience, and facilitate dramatic improvement in student academic achievement.